An outbreak of Providencia rettgeri bacteremia at a Ptyas mucosus farm in Hainan, China - Fan, Lixia; Pan, Jiwen; Zeng, Jifeng; Guo, Guiying; Yang, Nou; Li, Xuesong; Nafees Ur Rehman, Muhammad; Zheng, Jiping (Frontiers in Microbiology, 2024)
Aim: To describe the histopathology and etiology of an outbreak of respiratory disease at a Ptyas mucosus farm in Hainan, China. Methods and results: The etiology was confirmed by gross examination and microscopic analysis. The bacterial isolates from blood and internal organs were identified by biochemical analysis and 16S rRNA gene sequencing. The virulence and antibiotic resistance characteristics of the isolates were further demonstrated by polymerase chain reaction (PCR), disk diffusion testing, and LD 50 analysis in Kunming mice. Histopathological analysis of the diseased P. mucosus revealed systemic lesions, including severe airway obstruction with large numbers of inflammatory cells and cellulose exudates in the lungs; severe multifocal hepatocyte vacuolar degeneration and necrosis in the liver with excessive inflammatory exudates and chronic granuloma; splenic hemorrhage and partial loss of splenic structure; and renal vascular and interstitial congestion. Providencia rettgeri was isolated from the blood and multiple internal organs (liver, spleen, kidneys, and lungs). All examined isolates (H1, H4, and H13) were multidrug-resistant but sensitive to four antibiotics-cefepime, imipenem, chloramphenicol, and ciprofloxacin. Both H1 and H4 carried five resistance genes [bla OXA , tet(A), tet(B), tet(E), and aac (3)-IIa], whereas H13 only carried the tet(A) gene. The dominant virulence pattern of the three isolates was hlyA+ZapA+luxS+rsbA. The virulence of H1 strain was tested, and its 50% lethal dose (LD 50 ) in mice was 2.29×10 8 CFU ml -1 . Conclusion: To our knowledge, this is the first study to describe an outbreak of bacteremia caused by P. rettgeri in farmed rat snakes.Significance and impact of the study: The results highlight that P. rettgeri is an emerging bacterial pathogen in farmed reptiles.